Treatment of Subcutaneous Sarcoidosis with Hydroxychloroquine in a Hepatitis B Carrier Patient: A Case Report - Selma Erdoğan Düzcü; Yasin Hakan Kandil; Mualla Polat; Tuna Sezer (Düzce Tıp Fakültesi Dergisi)
Sarcoidosis is a disorder of unknown etiology affecting many systems and characterized by non-caseating granulomas. Subcutaneous sarcoidosis is the rarest form of specific lesions in cutaneous sarcoidosis. It occurs more frequently in the fourth decade of life and is more common in females than in males. Multiple asymptomatic to slightly painful, firm, mobile, round to oval, skin-colored, or erythematous nodules frequently occur in a bilateral and asymmetric pattern on the extremities. In the differential diagnosis, other diseases presenting with subcutaneous nodules should be excluded. Here, a case of subcutaneous sarcoidosis in a 51-year-old female hepatitis B carrier patient who partially responded to topical steroid treatment and was successfully treated with hydroxychloroquine was presented. In subcutaneous sarcoidosis, patients should be evaluated for systemic involvement. Hydroxychloroquine should be considered among the treatment options.